Brachytherapy Combined With or Without Hormone Therapy for Localized Prostate Cancer: A Meta-Analysis and Systematic Review - Zhou, Xueliang; Jiao, Dechao; Dou, Mengmeng; Chen, Jianjian; Han, Bin; Li, Zhaonan; Li, Yahua; Liu, Juanfang; Han, Xinwei (Frontiers in Oncology, 2020)
Abstract Purpose: The purpose of this study was to evaluate the efficacy of brachytherapy combined with or without hormone therapy in patients with localized prostate cancer. Methods and Materials: We systemically searched the Medline, Web of Science, Cochrane Library and Embase databases for studies published between the databases’ dates of inception and February 2019. The primary endpoints were the 5-year overall survival (OS) rates, 5-year biochemical progression-free survival (bPFS) rates and 10-year bPFS rates. The results were expressed as the relative risk (RR) and 95% confidence interval (CI). Based on the heterogeneity evaluated with the I2 statistic, a meta-analysis was performed using either a random- or fixed-effects model. Results: A total of 16 cohort studies including 9,359 patients met all the criteria for inclusion in the analysis. Our data showed that brachytherapy (BT) combined with hormone therapy (HT) increased the patients’ 5-year bPFS rates (RR = 1.04, 95% CI: 1.01-1.08, P = 0.005) and 10-year bPFS rates (RR = 1.12, 95% CI: 1.02-1.23, P = 0.001) compared with BT monotherapy. However, BT combined with HT did not increase the patients’ 5-year OS rates (RR = 1.02, 95% CI: 0.99-1.095, P = 0.1) compared with BT monotherapy. Conclusions: BT combined with HT can increase the bPFS rates of patients with localized prostate cancer, but it does not improve patients’ OS rates.